Digital Cartography in the Royal Library -the National Library of Sweden - Bäärnhielm, Göran (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Digital cartography - that is computer cartography - could be seen from several different viewpoints. Three aspects are important for libraries: digital map production, digital access and digital archiving.